Modul pembelajaran geometri berasaskan web bagi pelajar tingkatan 4 dan 5 menggunakan goegebra - Ya'acob, Alezar Mat (2010)
Geometry is an important branch of mathematics in secondary school mathematics lessons. This project is a learning module geometry using computer technology. This project was developed by using GeoGebra and website. GeoGebra is software used and the use of the website. GeoGebra and website will help students to improve mastery of geometry and computer skills more effectively. Students involved in this study are Form 4 and Form 5 students in one school in Johor that is Sekolah Menengah Permas Jaya Instruments used are questionnaires. Data obtained was analyzed using Microsoft Office Excel 2007. Hopefully GeoGebra and website can help students master the technology in computer skills and improve themselves in the geometry.